Analysis of Promotion Mix and Place in Increasing Sales at Murai Coffee Gunungsitoli - Wildan Syariah Farasi; Serniati Zebua; Martha Surya Dinata Mendrofa; Yuterlin Zalukhu (PT. Maju Malaqbi Makkarana, 2025)
This research is motivated by the phenomenon of cafe business competition in Gunungsitoli City, which demands effective marketing strategies, particularly in the utilization of promotional mixes and business location selection. The purpose of the study is to analyze how promotional mixes and location aspects play a role in increasing sales at Murai Coffee Gunungsitoli. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The research informants consisted of the owner, employees, and customers of Murai Coffee. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that Murai Coffee has implemented promotional strategies such as simple advertising, sales promotions, personal selling, public relations, and direct marketing that gradually increase customer interest. Meanwhile, the location factor, although not located in the city center, still provides sales opportunities through a comfortable atmosphere and quality service. However, challenges are still found in the comfort aspect, such as noise from outside and hot room temperatures, so that improvements to supporting facilities are needed. This research is useful for Murai Coffee in designing more optimal promotional strategies and location arrangements, for Nias University as a contribution to the development of marketing science, and as a reference for future researchers who want to study marketing strategies in the culinary sector.